Hall effect in the coma of 67P/Churyumov–Gerasimenko. Issue 2 (5th January 2018) - Huang, Z; Tóth, G; Gombosi, T I; Jia, X; Combi, M R; Hansen, K C; Fougere, N; Shou, Y; Tenishev, V; Altwegg, K; Rubin, M
Abstract: Magnetohydrodynamics simulations have been carried out in studying the solar wind and cometary plasma interactions for decades. Various plasma boundaries have been simulated and compared well with observations for comet 1P/Halley. The Rosetta mission, which studies comet 67P/Churyumov–Gerasimenko, challenges our understanding of the solar wind and comet interactions. The Rosetta Plasma Consortium observed regions of very weak magnetic field outside the predicted diamagnetic cavity. In this paper, we simulate the inner coma with the Hall magnetohydrodynamics equations and show that the Hall effect is important in the inner coma environment. The magnetic field topology becomes complex and magnetic reconnection occurs on the dayside when the Hall effect is taken into account. The magnetic reconnection on the dayside can generate weak magnetic field regions outside the global diamagnetic cavity, which may explain the Rosetta Plasma Consortium observations. We conclude that the substantial change in the inner coma environment is due to the fact that the ion inertial length (or gyro radius) is not much smaller than the size of the diamagnetic cavity.